Effect of smoking and type 2 diabetes on periodontitis narrative review of the literature (Salud, Arte y Cuidado, 2024)
Objective: to carry out a narrative review of the literature on the effect of smoking and type 2 diabetes on periodontitis. Methodology: A narrative review of the topic was carried out. An exhaustive search was carried out in the academic databases Pubmed Medline and Google Scholar, and other relevant sources. Keywords and search terms related to the topic were used. The criteria for including scientific articles were: a) written in English and b) 10 years to date. Results and discussion: Periodontitis is one of the most prevalent diseases worldwide. It involves complex dynamic interactions between specific bacterial pathogens, destructive host immune responses, modified by genetic and environmental factors. According to the Global Burden of Diseases study 2017, worldwide, 796 million people had severe periodontitis. Over the years, various studies have attempted to determine the risk factors involved in its appearance and the rapid progress of this disease. Patients with uncontrolled diabetes are at increased risk of developing periodontitis compared to systemically healthy patients or patients with well-controlled diabetes. The association is due in part to alterations in the immune system of patients with uncontrolled diabetes. Smoking is the most important environmental risk factor for periodontitis, it increases the risk of suffering from more severe periodontitis, causing greater gingival recession and rapid progression of the disease. In addition, the microbiome is altered in smoking patients. Conclusion: Diabetes and smoking have a negative impact on the occurrence, therapy and prognosis of periodontitis. Therefore, periodontitis patients should be advised of the importance of diabetes control and smoking cessation for the successful management of periodontitis
Keywords: periodontal diseases; periodontitis; diabetes mellitus; smoking habit